The current state of legal regulation of artificial intelligence in the Republic of Kazakhstan - Rustembekova, D.K.; Zhagalov, R.B. (Bulletin of the Karaganda University “Law Series”, 2026)
This study addresses the development of a cross-sectoral model for the legal regulation of artificial intelligence (AI) and highlights the transitional nature of the AI legal regime, situated between strategic innovation management and a fully developed system of legal accountability. The purpose of the study is to analyze the current state of AI regulation in the Republic of Kazakhstan, particularly in the context of civil liability for harm caused by AI systems. The methodological framework includes general and specialized scientific methods, such as analysis and synthesis, induction and deduction, as well as formal legal and comparative legal approaches. The paper provides a comprehensive analysis of current legislation in Kazakhstan related to AI regulation, identifies existing legal gaps, and proposes scientifically grounded measures to improve civil liability mechanisms in the context of AI technologies. It has been established that Kazakhstan has transitioned from software-oriented digitalization to the formation of a comprehensive legal regime for artificial intelligence. The findings indicate that Kazakhstan is transitioning from software-oriented digitalization to ward the formation of a comprehensive legal regime for AI. The results substantiate the need to improve civil liability for harm caused by AI systems and support the introduction of an additional provision into the Civil Code of the Republic of Kazakhstan.